Mr. Monk in trouble [large type] : a novel - Goldberg, Lee, 1962- (Monk series (New York, N.Y.), 2010)
Ever since a 1962 unsolved train robbery made it famous, people have made their way to Trouble in California's gold country - to search for the booty that train robbers supposedly dumped in the botched heist. When the museum watchman is murdered, Monk and his assistant, Natalie, are sent to investigate. Monk becomes obsessed with the legendary unsolved robbery, discovering a personal connection to the town's past. During the tail-end of the gold rush, Trouble's assayer was one Artemus Monk. Natalie can't help but notice the resemblance. But that might not be the only thing that ties the past to the present, and if Monk isn't careful, he'll learn how the town of Trouble lives up to its name.